Subject-Contextualism and the Meaning of Gender Terms - Dan Zeman (Journal of Social Ontology, 2022)
In this paper, I engage with a recent contextualist account of gender terms (particularly, “woman”) proposed by Díaz-León, E. 2016. “Woman as a Politically Significant Term: A Solution to the Puzzle.” Hypatia 31 (2): 245–58. Díaz-León’s main aim is to improve both on previous contextualist and non-contextualist views and solve a certain puzzle for feminists. Central to this task is putting forward a view that allows trans women who did not undergo gender-affirming medical procedures to use the gender terms of their choice to self-identify. My goal is to investigate Díaz-León’s proposal, point out (what I take to be) several shortcomings of the view and discuss possible replies on her part.